Effects of mutual intercropping on Pb and Zn accumulation of accumulator plants Rumex nepalensis, Lolium perenne and Trifolium repens. Issue 3 (16th March 2018) - Wen, Wen; Zhao, Huayin; Ma, Jianling; Li, Zhiqiang; Li, Hanhan; Zhu, Xuemei; Shao, Jirong; Yang, Zhanbiao; Yang, Yuanxiang; He, Fang; Liu, Yongfu
ABSTRACT: Intercropping is one of the most potential ways to remediate contaminated soil. In this study, three plants, including Rumex nepalensis which is a lead (Pb) accumulator plant, Lolium perenne which is tolerant to zinc (Zn) and a native plant Trifolium repens, were mutually intercropped in pots to study the effects of intercropping on co-remediation of Pb-Zn-contaminated soil from the Tangjia lead-zinc mine. Compared to the respective monoculture, the dry weights of R. nepalensis and T. repens were decreased under intercropping, while that of L. perenne was increased. The concentrations of total Zn in the three plants were increased by intercropping in which roots were higher than shoots. Besides, intercropping increased the accumulation of Zn in R. nepalensis and L. perenne per plant. The accumulations of heavy metals for R. nepalensis and T. repens in a single pot were enhanced by intercropping. Both of the maximum values of heavy metals' accumulation were produced by three-species intercropping (7819.31 μg/pot for Pb, 12576.05 μg/pot for Zn) in terms of a single pot. These results indicated that three-species intercropping could promote the phytoremediation efficiency for Tangjia lead-zinc mine, and thus further proved intercropping is an effective method to remediate the Pb-Zn-contaminated soil by R. nepalensis and T. repens .